Apropriação e expropriação da velhice como um dos elementos para a reprodução do capital - Pinholato, Aniele Zanardo (2013)
Considering the theory of labor value in Marx and, considering that the creation of value in capitalist society depends on consumption by the capital - the value of the use of the commodity labor power, this thesis sought to problematize the dual and contradictory movement of appropriation and expropriation of capital by old age. We conducted a literature review and documentary, from the Marxist referential, seeking dialogue with the authors from theoretical categories that provided relating aging and old age of the worker to the mundialização of the economy and capital restructuring, whose effects are to reveal the perverse world of work. Result of this approach the following issues: the myths and stereotypes that characterize old age as dependent, as synonymous of suffering and lack of physical beauty, they re gradually being overcome. The capitalist has realized that it is not strategic play such myths and stereotypes. Old age is a source of marketing possibilities and in this sense, is a source of realization of surplus value. The capital rotation and renovation of their cycles in the production process depend both on the exploitation of labor in the productive sphere, the consumption of goods. He guided the reflections, the formation of relative overpopulation. As a result of the historical movement, the elder nowadays not only inhabit the sphere of pauperism. Fruit of social struggle, the working class has won "the right to aging." By retirement or welfare policies through monetary transfer, the elders have income. This means that even in a situation of poverty and indigence, are also workers who pass by other forms of relative overpopulation. We conclude, finally, as indisputable fact, that the current and accelerated aging is changing the social relations: in capitalist accumulation and the responses of the state.